Young Moslem Consumers In Manado: Investigation of Satisfaction And Loyalty Toward Halal-Labeled Fast Food - Mamuaya, Nova Ch.; Pandowo, Aditya (JURNAL PENELITIAN, 2024)
This study aimed to explore the role of young Muslim consumer satisfaction as well as its antecedents and consequences. The sample study was 100 Muslim respondents who visited fast food restaurants at least twice last month and were 18-25 years old. Data collection was carried out using a questionnaire survey around the city of Manado. The analysis technique used is the Structural Equation Model with Partial Least Square. The results showed that halal labelling, perceived price, product quality, and satisfaction directly affected loyalty. The indirect effect shows that perceived price does not significantly influence loyalty through satisfaction. The results of this study prove that the relationship between young Muslim consumers' satisfaction with the halal label and product quality can strengthen their commitment